The young persons training programme : a qualitative study of the implementation of a transition education programme for young unemployed people in a New Zealand technical institute : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University - Korndörffer, Wanda Julie (Massey University, 1987)
The social relations of a capitalist mode of production engender contradictions that underpin the lived experience of individuals' daily practice. This practice thus becomes a site of struggle as agents confront structures within an arena of common sense, taken-for-granted assumptions about the nature of those social relations. In 1982, a participant observation study of one year's Young Persons Training Programme courses was carried out in one New Zealand technical institute. Participant observation, interviews and documentary analysis were used, within a method employing theoretical realism, to gain access to the ideas, practices and discourses that both contain, and are constructed in, a specific site of struggle: the production of training programmes for unemployed youth. This research focused on the links between social relations, discourse and practice, and used the case study in a reflexive way as material illustrative of particular social relations.
Keywords: Social relations; Unemployed youth; Training programmes; Transition education